Green Alternatives and National Energy Strategy The Facts behind the Headlines - Gallman, Philip G. (Johns Hopkins University Press, 2011)
It is no secret that the United States' dependence on oil-mostly foreign-puts the country in a precarious position. The United States needs innovative ways not only to power millions of automobiles on its highways but also to secure sustainable sources of fuel for the future. This book presents the latest facts and figures about alternative energy to any physicist, engineer, policymaker, or concerned citizen who needs a reliable source of information on the nation's looming energy crisis. Philip G. Gallman focuses especially on green vehicles and the interrelationship between their design and various energy sources. He explains simply and clearly the complex energy and automotive engineering issues involved in developing green vehicles, measures their likely effect on energy resource demand, and considers what they might mean for national energy strategy. Addressing problems associated with renewable resources often overlooked or ignored in the popular press, Gallman explains what replacing oil with alternative sources of energy realistically entails. Can the nation satisfy its energy demands with wind turbines, solar power, hydroelectric power, or geothermal power? Is biodiesel or electricity the answer to our gas-guzzling ways? Organized logically and with an accessible narrative, Green Alternatives and National Energy Strategy guides readers through the essential questions and hurdles the United States must answer and overcome to transition from a petroleum-dependent nation to one that runs on sustainable, renewable energy.